2022
DOI: 10.1021/acs.macromol.2c01228
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Poly(disulfide) Synthesis in the Presence of Organocatalysts

Abstract: An organocatalyst-mediated, extremely rapid, robust, and practical poly(disulfide) synthesis method is introduced to polymer chemistry. A variety of organocatalysts were initially screened using commercially available 1,6-hexanedithiol and diisopropyl azodicarboxylate (DIAD) to reveal the best catalyst for the process. Remarkably, although a very low amount of catalyst loading (5%), all the catalysts examined afforded poly(disulfide) in 1 min with low to high molecular weights. Among them, triphenylphosphine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Sulfhydryl groups are valuable tools in organic chemistry, 9 materials science, 10 and biochemistry 11,12 owing to their abilities to rapidly and selectively react with specific functional groups under mild conditions. In addition to their well-known thiol−ene 13−15 and disulfide-formation 16,17 chemistries, sulf-hydryl groups have also been used to form self-assembled monolayers (SAMs) on Au surfaces through Au−S bonds. 18−20 Polymers bearing sulfhydryl groups at their chain end have been successfully synthesized, 10 thereby providing a convenient platform for further functionalization, 21−24 the introduction of diverse functional groups, 25−28 and the formation of block copolymers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Sulfhydryl groups are valuable tools in organic chemistry, 9 materials science, 10 and biochemistry 11,12 owing to their abilities to rapidly and selectively react with specific functional groups under mild conditions. In addition to their well-known thiol−ene 13−15 and disulfide-formation 16,17 chemistries, sulf-hydryl groups have also been used to form self-assembled monolayers (SAMs) on Au surfaces through Au−S bonds. 18−20 Polymers bearing sulfhydryl groups at their chain end have been successfully synthesized, 10 thereby providing a convenient platform for further functionalization, 21−24 the introduction of diverse functional groups, 25−28 and the formation of block copolymers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The conventional methods for poly­(disulfide) synthesis include oxidative polycondensation of dithiols, , thermally induced polymerization in bulk, , and disulfide exchange. , Some approaches circumvent the direct construction of S–S bonds by polymerization of monomer with preinstalled disulfide bonds , or copolymerization with sulfur . Recently, the anionic ring-opening polymerization (ROP) of 1,2-dithiolanes has emerged as a promising method to synthesize poly­(disulfide)­s in a more controlled manner. , Liu and Moore found that using a thiolate initiator (RS – ) with high nucleofugality in the anionic ROP led to poly­(disulfide)­s with a cyclic topology .…”
Section: Introductionmentioning
confidence: 99%
“…The conventional methods for poly(disulfide) synthesis include oxidative polycondensation of dithiols, 42,43 thermally induced polymerization in bulk, 44,45 and disulfide exchange. 46,47 Some approaches circumvent the direct construction of S−S bonds by polymerization of monomer with preinstalled disulfide bonds 48,49 or copolymerization with sulfur.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hence, the development of concise and highly effective pathways to access poly(disulfide)s have received great attention over the past decades. Various methods including oxidative coupling of thiols [ 16 , 17 , 18 , 19 ] and polymerization of disulfide-containing monomers [ 8 , 20 , 21 , 22 , 23 , 24 , 25 ] have been developed for the synthesis of poly(disulfide)s. Besides the synthesis of poly(disulfide)s with repeating disulfides, little success has been made in incorporating a low content of disulfides into the main chain of commodity polymers [ 19 , 26 ].…”
Section: Introductionmentioning
confidence: 99%